Antenas adaptativas para sistemas de comunica??es - Faria, Vagner Vilela de (2004)
Adaptive antennas are radiating systems that allow the control of the shape and direction of the irradiation diagram. With this, they are able to guide the main wolf of the radiation pattern to the desired signal and simultaneously reduce the influence of the interfering signals. These systems present a marked demand in 3G and 4G technologies of the mobile cellular system. This makes it possible to increase the channel capacity of the system. So, this work presents a theoretical study of this system and the computer simulations based on the proposed theories. The study is based on obtaining the signal from a plane wave that reaches a linear network of radiating elements. In this network, processing parameters, known as weights, are introduced that allow adjusting the phase and amplitude of the transmitted / received signal. The adjustments are made by a digital signal processor that, through special algorithms, update the network weights in function of the directions of the desired signal and the suppression of the interferences. In the calculations and in the simulations the mathematical algorithms and functions are used that describe the control of the irradiation diagram obtained in the diagrams